(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Estimation of the total cost is essential for the planning and the designing of pipelines in a cost-effective way. As a result, the total cost modelling could go beyond the established objectives of least-cost design and optimization. This study incorporates a design methodology for pipelines transporting spherical capsules, which have variant sizes and densities. A methodology has been developed to determine the optimal size and lifetime of pipelines transporting solid–liquid mixtures (Capsule Flow). The methodology includes a model for the prediction of various life-cycle costs. The methodology provides a closed form solution to predict the optimal pipe diameter corresponding to the least total cost. Such solutions are obtained for different life-cycle costs, of which the one associated with minimum annual total cost provides the lifetime. The developed methodology has been used to obtain the optimal diameter of a pipeline for a practical case. The study reveals the interrelationship between the optimal pipe diameter and the corresponding minimum total cost.